Finding Your Place in Science: Factors Influencing Students' Decision in Choosing Science as a Subject to Study - N.N. Azizah (Jurnal Pengajaran MIPA, 2021)
Studies have uncovered that educators, scientists, and policymakers are concerned that students' interest in pursuing science has grown visibly smaller. Recent Indonesian Ministry of Education data even suggested that the number of students enrolled in science majors was only a fifth of students enrolled in economics majors. This paper investigated factors contributing to why students' decided to pursue science majors as subjects to study and how these factors illuminated the steps that can be taken to improve how students see science and renew their faith and interest in pursuing science for their future careers.